2018
DOI: 10.1364/ol.43.003586
|View full text |Cite
|
Sign up to set email alerts
|

Integrated waveguides and deterministically positioned nitrogen vacancy centers in diamond created by femtosecond laser writing

Abstract: Diamond's nitrogen vacancy (NV) center is an optically active defect with long spin coherence times, showing great potential for both efficient nanoscale magnetometry and quantum information processing schemes. Recently, both the formation of buried 3D optical waveguides and high-quality single NVs in diamond were demonstrated using the versatile femtosecond laser-writing technique. However, until now, combining these technologies has been an outstanding challenge. In this Letter, we fabricate laser-written ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Subsequently it was shown that NV center fluorescence could be collected through the waveguide by selectively exciting one of the single NV centers through the confocal microscope. Photoluminescence excitation studies of the NV centers at 6K demonstrated that although they did not have lifetime limited linewidths, they were comparable to the linewidths reported by the Salter group at the upper end of their laser writing energy range . Previous measurements of as grown NV ensembles in waveguides showed that the NV centers retain their spin coherence .…”
Section: Deterministic Placement Of Color Centerssupporting
confidence: 78%
See 1 more Smart Citation
“…Subsequently it was shown that NV center fluorescence could be collected through the waveguide by selectively exciting one of the single NV centers through the confocal microscope. Photoluminescence excitation studies of the NV centers at 6K demonstrated that although they did not have lifetime limited linewidths, they were comparable to the linewidths reported by the Salter group at the upper end of their laser writing energy range . Previous measurements of as grown NV ensembles in waveguides showed that the NV centers retain their spin coherence .…”
Section: Deterministic Placement Of Color Centerssupporting
confidence: 78%
“…In order to achieve this, the Eaton group wrote waveguides in quantum grade diamond at 25 µm depth with a line of 5 single static exposures separated by 20 µm at the center of each waveguide. Following annealing at 1000 ° C, fluorescence confocal microscopy measurements confirmed that single NV centers had been created at several of the expected static exposure sites, and importantly the waveguides survived the annealing process . Concentrating on NVs written with 28 nJ, it was shown that it is possible to excite the single NV centers by coupling a laser beam into the waveguide through a single mode fiber.…”
Section: Deterministic Placement Of Color Centersmentioning
confidence: 92%
“…Using the characterization setup described in Hadden et al [111], initial photoluminescence imaging performed on the waveguides showed single NV emission from 2 out of the 5 spots, represented as NV2 and NV4 in figure 15(a). NV2 was chosen for further characterization.…”
Section: Femtosecond Laser Inscribed Integrated Quantum Photonic Chipmentioning
confidence: 99%
“…Another route was recently reported using deterministic positioning of a laser‐written NV center inside a buried waveguide generated by laser writing in bulk diamond . However, the large mismatch between waveguide mode (≃5.8 μm) and the focused laser excitation spot (≃0.6 μm) on the NV center limited the measured count rate to ≃10 counts per second.…”
Section: Coupling Color Centers To Photonic Structuresmentioning
confidence: 99%